Retrospection on Digital Technology in the Field of Education - Rachana Jaiswal (AG Volumes, 2022)
The impact of digital technology on our daily lives has increased, but it has become more apparent to students in our educational system... This can be seen in the increasing use of technology by students, from smartphones and tablets to laptops and other portable electronic devices. Students' increasing reliance on technology has led to an increase in the use of smart boards, computer labs, and online curricula in the classroom. Cyberbullying and plagiarism may be drawbacks of some forms of technology, but these are minor compared to all of the benefits that can be gained from using technology in education. Teachers can use digital technology to help them develop curriculums, to help students work more efficiently, and even to help kids find common ground between the lives they lead at school and at home. Additionally, it has been influenced by the spread of digital technology in education around the world. There is a wealth of information available online that does not limit students to a single point of view. Teaching a lesson can be made more clear and understandable with the help of audio or visual aids.